Fiji's largest marine reserve benefits reef sharks - Goetze, Jordan; Fullwood, L. (Springer Verlag, 2013)
To provide more information about whether sharks benefit from no-take marine reserves, we quantified the relative abundance and biomass of reef sharks inside and outside of Namena, Fiji's largest reserve (60. 6 km2). Using stereo baited remote underwater video systems (stereo-BRUVs), we found that the abundance and biomass of sharks was approximately two and four times greater in shallow and deep locations, respectively, within the Namena reserve compared to adjacent fished areas. The greater abundance and biomass of reef sharks inside Namena is likely a result of greater prey availability rather than protection from fishing. This study demonstrates that marine reserves can benefit sharks.